Design, mindfulness & estresse: desenvolvimento de um artefato de meditação mindfulness para redução do estresse - Paz, Eriwelton (2018)
The present work aims at the development of an artifact that serves as an aid to the practice of mindfulness, with a purpose to the attenuation of stress levels. For this, the concept of stress and its manifestations on the body are presented, followed by a general apparatus of mindfulness as a meditation technique, considering its historical context, its practice and its impacts: physical, emotional and psychic. The research also brings a bibliographic survey of studies and theories in design that can interfere in the cognitive and emotional aspects of the individual. The project is based on the structure of the experimental methodology of Gui Bonsiepe (1984) with adaptation of this and inclusion of some other methods, aiming to fit to the actual object of this research. At the end, it is presented the design of a home use artifact that simulates the respiratory movements through an LED circuit, working the perception of the environment through the change of colour, in an attempt to stimulate the concentration in the breath, making the environment more propitious to the practice of mindfulness.